PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 25 SIJUNJUNG - Ermawati Arief, Meutia Yetisia, Emidar, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is (1) to determine the level of skills to writing news of students VIII SMPN 25 Sijunjung without using problem based learning aided media images series. (2) to determine the level of skills to writing news of students VIII SMPN 25 Sijunjung by using assisted problem based learning aided images series. (3) analyze the effect of applications of problem based learning model of media assisted drawing writing skills news students VIII SMPN 25 Sijunjung. This type of research is quantitative with experiment methode. The use of problem based learning model aided media images series affect the skills to writing news students VIII SMPN 25 Sijunjung.Â Kata kunci: Â pengaruh, model problem based learning berbantuan media gambar berseri, menulis berita